Uncertainty Quantification in Irreversible Electroporation Simulations - Nicholas Labarbera (Bioengineering, 2017)
One recent area of cancer research is irreversible electroporation (IRE). Irreversible electroporation is a minimally invasive procedure where needle electrodes are inserted into the body to ablate tumor cells with electricity. The aim of this paper is to investigate how uncertainty in tissue and tumor conductivity propagate into final ablation predictions used for treatment planning. Two dimensional simulations were performed for a circular tumor surrounded by healthy tissue, and electroporated from two monopolar electrodes. The conductivity values were treated as random variables whose distributions were taken from published literature on the average and standard deviation of liver tissue and liver tumors. Three different Monte Carlo setups were simulated each at three different voltages. Average and standard deviation data was reported for a multitude of electrical field properties experienced by the tumor. Plots showing the variability in the electrical field distribution throughout the tumor are also presented.